Distribution of Cd (II) Between Buffered Aqueous Solutions and Chloroform Solution of 4,4´-(1e,1e´)-1,1´-(ethane-1,2-diylbis(azan-1-yl-1ylidene)bis(5-methyl-2-phenyl-2,3-dihydro-1h-pyrazol-3-ol) (H2BuEtP) - Godwin, J.; Tella, L. S. (European Journal of Applied Sciences, 2023)
The distribution of Cd(ll) between buffered aqueous solutions and chloroform solution of 4,4´-(1e,1e´)-1,1´-(ethane-1,2-diylbis(azan-1-yl-1ylidene)bis(5-methyl-2-phenyl-2,3-dihydro-1h-pyrazol-3-ol) (H2BuEtP) and the effect of 1-(3-hydroxy-5-methyl-2-phenyl-2,3-dihydro-1h-pyrazol-4-yl) butan-1-one (HBuP) as a synergist in the distribution was studied. The concentration of Cd (ll) in aqueous phase after shaking was determined with an Atomic Absorption Spectrophotometer at wavelength of 228nm and the distribution determined by difference. pH 4. 75 - 7.5 was the range in which > 90% distribution of cadmium into organic phases occurred. Slope analysis was used to predict the probable extraction reactions and also the distributing cadmium complexes as Cd(HBuEtP)X and Cd(HBuEtP.BuP) respectively. HBuP slightly increased the pH1/2 from 3.87 ± 0.18 to 4.88 ± 0.12 and partition coefficient KD from 2.19 ± 0.35 to 3.15 ± 0.42. However, the extraction constant Kex2Cd ((-10.09 ± 0.09) in the presence of HBuP was < Kex1Cd (-3.01± 0.9) for H2BuEtP alone. It was recommended that kinetics studies and effect of acids, anions and auxiliary complexing agents on the distribution of cadmium be investigated to fully evaluate the potentials of H2BuEtP in the extraction of cadmium from aqueous media.